Aspectos socioeducativos relacionados al índice de caries de la nacionalidad amazónica Zápara. - Pazmiño Moyano, Heidy Mishell (2025)
Dental caries is a chronic multifactorial disease that causes demineralization and destruction of hard tooth tissues. The objective was to analyze the socio-educational aspects related to the caries index of the Zápara nationality in Ecuador. This was a descriptive cross-sectional study with a quantitative approach, in which observation and surveys were used as techniques. The population consisted of 61 patients of Zápara nationality, belonging to the Comprehensive Oral Health Program for the Waorani nationality (Ecuador) research group called Dentistry in Action. They were selected through non-probabilistic convenience sampling based on selection criteria. The caries index did not show statistically significant differences with respect to the type of Amazonian indigenous nationality; however, the caries index was associated with age. It was concluded that, regardless of the type of Amazonian nationality, caries was present and increased with the age of the population.